1988
DOI: 10.1007/bf01736521
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal responsiveness to human atrial natriuretic peptide (hANP) in normotensive patients with type 1 diabetes mellitus

Abstract: Potential impairment of the efficacy of human atrial natriuretic peptide (human ANF-(99-126), hANP), the most potent endogenous natriuretic agent in healthy subjects, was examined in eight male normotensive patients with uncomplicated type 1 diabetes mellitus (aged 22-37 years). After giving informed consent, patients and eight male control subjects (aged 22-28 years) received in a random double-blind study design i.v. bolus injections of 100 micrograms hANP (Bissendorf peptide) or placebo. At base-line, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…(1989) found significant decreases in low density lipoproteins in nondiabetic hypertensive patients but not in diabetic patients with similarly elevated high blood pressure. Jungmann et al (1988) reported an impairment of the renal action of human atrial natriuretic peptide in 100M patients with hyperglycaemia, but not in similar patients with well controlled blood glucose concentrations (Jungmann et at. 1989).…”
Section: Pharmacodynamicsmentioning
confidence: 96%
“…(1989) found significant decreases in low density lipoproteins in nondiabetic hypertensive patients but not in diabetic patients with similarly elevated high blood pressure. Jungmann et al (1988) reported an impairment of the renal action of human atrial natriuretic peptide in 100M patients with hyperglycaemia, but not in similar patients with well controlled blood glucose concentrations (Jungmann et at. 1989).…”
Section: Pharmacodynamicsmentioning
confidence: 96%
“…Water immersion as well as an intravenous sodium load, both methods used to induce increments in endogenous ANF concentrations, exerted an impaired diuretic and natriuretic response in diabetic patients compared with control subjects (7,8), and similar results were obtained after exogenous ANF administration (10,11).…”
mentioning
confidence: 58%
“…Consequently, the BP response to ANF infusion cannot be considered to be a representative parameter for the direct vascular effects of ANF. Therefore, none of the previous observations on the systemic effects of ANF (10,11,17) can solve the question whether the direct vascular effect of ANF is changed in diabetes. These observations convincingly show for the first time that uncomplicated human IDDM is associated with an impaired vasodilator response to the endogenous hormone ANF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Diabetes is another condition characterized by a high plasma A N P and reduced responsiveness of the kidney to exogenous A N P [133][134][135]. Studies showed that cardiac A N P synthesis is augmented in streptozotocin-induced rats, which could be reversed with insulin therapy [136], Increase in plasma A N P is felt to be secondary to the volume expansion induced by hyperglycemia [137].…”
Section: Diabetes Mellitusmentioning
confidence: 99%